Kecacingan, malaria, dan status besi ibu hamil di Kabupaten Batang Hari Provinsi Jambi - Helfiyan Helfiyan; Hamam Hadi; Siti Helmyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background: Anemia among pregnant women may increase abortion, premature, low birth weight and even mortality before and after delivery. Factors causing anemia in Indonesia are lack of Fe, inadequate intake, demanding needs, and lack of nutrient facilitating Fe absorption. Besides, infection such as worm and malaria may cause anemia as well. Result of household health survey 2001 stated that prevalence of pregnant women with anemia was 40% in Indonesia. In Jambi Province, it was 39% in 2003 and 42.3% for Batang Hari Regency while infection of malaria was 50.0% in all age groups and many other districts that its environment were woods, humid, and wasted that may increase infection of hookworm.Objective: The study was proposed to know the correlation of hookworm, malaria with anemia among pregnant women by analyzing correlation of hookworm, malaria, and anemia and correlation of hookworm, malaria and Fe status among pregnant women.Method: This was cross sectional study. It held from September until December 2005 in Batang Hari Regency, Jambi Province. Subjects were 132 pregnant women. Examination of blood for Hb, malaria and ferritin were taken together while feces were later.Results: There were no significant correlation of Ascaris lumbricoides infection with anemia (p = 0.36; OR = 2.43), Trichiuris thrichiura infection with anemia (p = 0.30), 2 kinds of worm Ascaris lumbricoides + Trichiuris trichiura with anemia (p = 0.08; OR = 4.87), and infection of Ascaris lumbricoides + Necator americanus with anemia (p = 0.30). There was significant correlation of 3 kinds of worm Ascaris lumbricoides + Trichiuris trichiura + Necator americanus with anemia (p = 0.018; OR = 7.3). There were no significant correlation of Ascaris lumbricoides with ferritin (p = 0.17; OR = 3.23) and Trichiuris trichiura with ferritin (p = 0.25). There was significant correlation of 2 kinds of worm Ascaris lumbricoides + Trichiuris trichiura with ferritin (p = 0.04; OR = 6.4). There was no significant correlation of Ascaris lumbricoides + Necator americanus with ferritin p = 0.25. There were significant correlation of 3 kinds of worm (Ascaris lumbricoides + Trichiuris trichiura + Necator americanus) with ferritin p = 0.007; OR = 9.69 and ferritin with anemia p = 0.0001; OR = 17.45.Conclusion: There was no significant correlation of hookworms Ascaris lumbricoides, Trichiuris trichiura, Ascaris lumbricoides + Trichius trichiura, Ascaris lumbricoides + Necator americanus with anemia. There were significant correlation of infection of Ascaris lumbricoides + Trichiuris trichiura + Necator americanus with anemia and malaria with anemia. There was no correlation of hookworms Ascaris lumbricoides, Trichiuris trichiura, Ascaris lumbricoides + Neca- tor americanus with anemia. There were correlation of infection Ascaris lumbricoides + Trichiuris trichiura and Ascaris lumbricoides + Trichiuris trichiuris + Necator americanus with ferritin, malaria with ferritin, and ferritin with anemia.